I—Memory from Plato to Damascius. (20th June 2019) - Adamson, Peter
Abstract: Taking its cue from a passage in which the late pagan Neoplatonist Damascius criticizes his predecessor Proclus, this paper explores the way that ancient philosophers understood the soul's access to its own tacit contents through the power of memory. Late ancient discussions of this issue respond to a range of passages in Plato and to Aristotle's On Memory . After a survey of this material it is shown that for Damascius, but not Proclus, memory requires a distinction between the subject and object of remembering. This means that there can be no memory involved in self-thought, such as occurs in intellect, but only in soul. In conclusion, the paper draws attention to a parallel discussion in Augustine, who, like Proclus, thinks that self-thinking can be understood as a function of memory.